(untitled) (Research, Society and Development, 2022)
The main aim of this study was to analyze possible relationships between the proposed actions, priorities, and investments of the São Francisco River Basin Water Resources Plan, with the 169 targets and 232 indicators of the 17 Sustainable Development Goals (SDGs) from United Nations 2030 Agenda’s, dated from 2015. This analysis pointed out which performance indicators would be more appropriate for the hydro environmental assessment of the basin in the current context. For this purpose, information was collected through consultation with official institutions operating in the management of water resources in the basin. The results obtained showed the existence of a direct relationship between the actions of the Water Resources Plan for the São Francisco River Basin (PRH-SF) with the SDGs 1, 2, 3, 6, 7, 8, 11, 12, 13 and 15, emphasizing SDG 6 – water and sanitation, which among the 42 actions of the investment plans the SDG 6 indicators related to 26 of them. It is also noteworthy that the indicators analyzed from SDG 6 directly reflect on a better performance of SDGs indicators, all connected to each other. Therefore, the relationship presented in this study, between the proposed actions, priorities, and investments of the São Francisco River Basin Water Resources Plan and the UN 2030 Agenda SDGs, contributed to a better understanding of the existing dialogue between water resources management and global strategies sustainable development.